Implementation of Bayes’ Theorem Method for Diagnosing Diseases in Plants Daucus Carota L (Carrot) - Sinaga, Sennaria Lia Sukhaesi; Robby; Hendri (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2025)
Carrot is a biennial plant known for its ability to store large amounts of carbohydrates and flower in the second year. In addition to being a food ingredient, carrots offer various health benefits, especially for vision. Rich in nutrients, carrots are known as a source of pro-vitamin A (beta-carotene) and various other essential nutrients. Common diseases that affect carrots include leaf spots, alternaria rot, and root-knot nematodes. To address the issues related to carrot plant diseases, a system is needed that can assist in diagnosing the symptoms of these diseases on the plants. The design of an expert system for diagnosing diseases in carrots is very important. This system can match symptoms with existing rules and generate clinical diagnoses based on the developed knowledge base, using Bayes’ Theorem. The result of this research is that farmers can better understand how to manage diseases in carrot plants to prevent losses. Not only farmers, but also novice gardeners interested in horticulture can utilize this expert system application to make the planting process more effective and produce high- quality carrots.